A Philosophical Dictionary, Volume 09 - Voltaire, 1694-1778; Leigh, Oliver Herbrand Gordon; Morley, John, 1838-1923; Smollett, T. (Tobias), 1721-1771; Fleming, William F. (Salt Lake City, UT : Project Gutenberg, 2011)
"A Philosophical Dictionary, Volume 09" by Voltaire is an encyclopedic dictionary published in 1764. This alphabetically arranged work challenges religious and social institutions through essays that critique the Catholic Church, Judaism, Islam, and other establishments. Originally released anonymously as a portable, affordable text, it represents Voltaire's lifelong effort to educate and provoke. The work champions deism, tolerance, and freedom of the press while addressing injustices inspired by events like the Calas affair. Though publicly embraced and quickly sold out, religious authorities condemned it, burning copies across Europe. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Dictionnaire_philosophique
Release date is 2011-03-28
Produced by Andrea Ball, Christine Bell & Marc D'Hooghe (From images generously made available by the Internet Archive.)
Keywords: Philosophy -- Dictionaries; Criticism (Philosophy)